Nitride thin films grown by thermal laser epitaxy - Dong Yeong Kim; Varun Harbola; Seungwon Jung; Jinjoo Lee; Sukanya Roy; Felix V. E. Hensling; Lena N. Majer; Hongguang Wang; Peter A. van Aken; Joao Marcelo J. Lopes; Neha Aggarwal; Jochen Mannhart; et al. (APL Materials)
The growth of a wide range of binary nitride films with excellent properties is reported. These films are deposited by thermal laser epitaxy (TLE). If equipped with CO2–laser substrate heating, TLE allows growth temperatures ≫ 1000 °C combined with strong nitriding conditions, which are established by using ammonia (NH3) gas as a nitrogen precursor. Films deposited on c-plane sapphire substrates include semiconducting nitrides (BN, AlN, ScN, and YN), superconducting nitrides (TiN, VN, ZrN, and NbN), and magnetic nitrides (CrN and GdN). The superconducting transition temperatures of TiN, VN, ZrN, and NbN films are 5.7, 8.9, 8.9, and 16.9 K, respectively. The Néel temperature of CrN films is ≃280 K, and the Curie temperature of GdN films is 66 K; both lie within the reported ranges. The controlled fabrication of different phases of individual nitride compounds is explored, revealing that subnitride phases can be grown at lower NH3 pressures. This study also demonstrates the heteroepitaxial growth of multilayer nitride films on c-plane sapphire.